KONSEP PEMBIASAAN (RIYADHAH) DALAM PENDIDIKAN KARAKTER MENURUT AL GHAZALI - Zulfahmi; Agustianda; An Nu'man; Siti Mahmudah Noorhayati (PT. Hasba Edukasi Mandiri, 2026)
This study discusses the concept of habituation (riyadhah) in character education according to Imam Al Ghazali and its relevance to modern education. The research employed a qualitative-descriptive approach using the library research method through the study of Al Ghazali’s works, especially Ihya’ ‘Ulumuddin, along with various related studies. The findings reveal that riyadhah is a method of spiritual training carried out gradually, consistently, and continuously so that virtuous values become ingrained habits within individuals. According to Al Ghazali, character education aims to develop noble morals oriented toward faith and devotion to Allah while also shaping good personality traits in social life. The implementation of riyadhah can be carried out through role modeling, habituation of worship, supervision, and advice within the family, school, and community environments. This study also finds that the success of riyadhah-based character education is strongly influenced by the synergy and consistency of all educational environments. The inhibiting factors include lack of parental supervision, limited religious education in schools, social environmental influences, and weak role models. Therefore, Al Ghazali’s concept of riyadhah remains highly relevant in fostering religious, disciplined, and noble character in the modern era.